Adapting the Existential Gratitude Scale to Turkish: A Measure of Gratitude in Painful Times - Hale ÇANAKÇI; Halil EKŞİ (Spiritual Psychology and Counseling)
This study aims to adapt the Existential Gratitude Scale (Jens-Beken & Wong, 2019) to Turkish culture and to examine the scale’s psychometric properties in this respect. The study uses the convenience sampling method, and the sample consists of 286 participants between the ages of 18 to 53, of whom 212 (74.1%) are female and 74 (25.9%) are male. The structural validity of the scale has been examined using confirmatory factor analysis (CFA). The CFA results confirm the original EGS’ one-dimensional structure over a Turkish sample, and the scale has good fit indices (χ2=94.655, df=34, χ2/df =2.784, GFI=0.936, NFI=0.930, CFI=0.954, SRMR=0.0420, and RMSEA=0.079). The factor loadings range from .46 to .77. For the criterion validity, Pearson correlations were calculated for the EGS with the Short Gratitude, Resentment, and Appreciation Scale and Transpersonal Gratitude Scales, which resulted in significant positive correlations (respectively r=0.476 and r=0.579 at p= 05). The item-total correlation and comparison of the upper 27% and lower 27% groups were examined for the item analysis of the scale; these have revealed the EGS to possess satisfactory discriminating power. As a result of the reliability analysis, Cronbach’s alpha of internal consistency was calculated as .893. This study shows the EGS to be a valid and reliable tool useable in the context of Turkey for measuring individuals’ existential gratitude levels. The EGS can be a valuable tool for practitioners in mental health settings in developing appropriate interventions for individuals’ coping skills in celebrating adversity.